Acute kidney injury caused by systemic Neisseria gonorrhoeae infection after successful kidney transplantation - Harada, Hiroshi; Mitsuke, Akihiko; Fukuzawa, Nobuyuki; Kodama, Fumihiro; Hirose, Takayuki; Tanaka, Toshiaki; Imamoto, Teppei; Tanaka, Hiroshi (Transplant Infectious Disease, 2018)
Neisseria gonorrhoeae is one of the microbes that can causes male urethritis. This microbe is most likely to be transmitted via sexual intercourse. In men, the representative infection sites are the urethra, and oral mucosa but gonococcemia is rere. We present a case of gonococcemia in a 47‐year‐old male successful kidney recipient. He temporarily lost his graft function due to acute kidney injury followed by sepsis; however, short‐course intermittent hemodialysis and long‐term intensive ceftriaxone inoculation saved his life and his graft function.